Effects of PGPR, AMF and Trichoderma Applications on Adaptation Abilities to Different Biotic and Abiotic Conditions in Medicinal and Aromatic Plants - Ebru Şirin; Yaşar Ertürk; Ahmet Kazankaya (Turkish Journal of Agriculture: Food Science and Technology)
Medicinal and aromatic plants are valuable sources of herbal products worldwide due to their secondary metabolite content, high antioxidant activities and many other biological activities. As a result of the developing technology, the demand for natural active substances obtained from plants has increased. For use, plants collected from nature do not have the desired quality standards. For this reason, sustainability can be achieved by using microbial inoculants as well as many biotechnological and molecular approaches such as micro propagation, synthetic seed technology to increase the yield and quality standards of medicinal and aromatic plants. Thanks to microbial inoculants, yield increase can be realized and at the same time, product quality can be contributed due to increased soil quality. In this review, it was aimed to evaluate the important roles of plant growth promoting rhizobacteria (PGPR), Arbiscular mycorrhizal fungi and Trichoderma inoculants in increasing productivity, nutrient uptake and resistance of medicinal and aromatic plants to environmental stresses in the light of literature. In this review, the variation in the resistance of plants to environmental stresses is summarized by evaluating the ultimate effects of microbial inoculants alone and in combination. In addition, it has been added to the evaluation in studies to prevent the decrease of secondary metabolite content formed under environmental stress conditions in medicinal and aromatic plants by microorganisms.